2009
DOI: 10.1590/s0104-11692009000200003
|View full text |Cite
|
Sign up to set email alerts
|

Puerperal women's perceptions on vertical and horizontal deliveries

Abstract: This qualitative study aims to better understand the perceptions of puerperal women regarding their experiences in vertical and horizontal deliveries and identify positive and negative aspects of each position. Semi-structured interviews were carried out with ten puerperal women hospitalized in the rooming-in unit of a teaching hospital. After thematic analysis - Collective Subject Discourse - positive aspects of the vertical position emerged, namely: greater comfort, freedom of movement, reduction of the expu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…26 A qualitative study conducted in a teaching hospital in Santa Catarina State, analyzed the perception of puerperal women of giving birth in a vertical or horizontal position and concluded that women considered the vertical position to be more positive because it favors movement, is more adequate for pushing and expelling the fetus, in addition to enabling them to have greater participation in childbirth. 27 In this context, it should be noted that knowledge about childbirth should be imparted from the beginning of prenatal care and, when it is reinforced throughout pregnancy up until delivery, it can provide pregnant women and their companions with empowerment and autonomy fitting for parturition, positively influencing the way in which they all experience the accomplishment of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…26 A qualitative study conducted in a teaching hospital in Santa Catarina State, analyzed the perception of puerperal women of giving birth in a vertical or horizontal position and concluded that women considered the vertical position to be more positive because it favors movement, is more adequate for pushing and expelling the fetus, in addition to enabling them to have greater participation in childbirth. 27 In this context, it should be noted that knowledge about childbirth should be imparted from the beginning of prenatal care and, when it is reinforced throughout pregnancy up until delivery, it can provide pregnant women and their companions with empowerment and autonomy fitting for parturition, positively influencing the way in which they all experience the accomplishment of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the horizontal position makes these aspects difficult. As the movements are limited it causes suffering, fatigue, longer duration of the expulsive period and usually more occurrence of obstetric interventions [16].…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio cualitativo llevado a cabo en Brasil que incluyó las percepciones de mujeres respecto a sus vivencias en el parto vaginal, se determinó que los aspectos positivos de la posición horizontal fueron la reducción en su tiempo de duración y una mayor sensación de seguridad y apoyo por parte del personal médico, mientras que los aspectos negativos se relacionaron con la incomodidad y la dificultad para ejercer la fuerza. Dentro de algunos aspectos positivos de la posición vertical y los aspectos negativos de la posición horizontal se destacaron con mayor intensidad y frecuencia, y están de acuerdo con la evidencia científica (27).…”
Section: Continente Americanounclassified